Apiaceae and Autism - Williams, Sally (Homœopathic Links, 2017)
This article discusses the use of remedies from the Apiaceae order of plants in cases pertaining to autism.
Keywords: Apiaceae; Apiales; Umbelliferae; Autism; Infection; Vaccination; PANDAS; Sanicula europaea